A dry masonry rendering mortar for home decoration and a preparation method thereof
Patent Information
- Application Number
- CN202611132987.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-20
AI Technical Summary
其主要原因在于,传统素砂浆的保水性能不足,导致水泥水化不充分、界面粘结强度低,同时砂浆收缩大,易产生开裂
1、本发明从多维度提升水泥的保水性能。通过适当提高家装水泥熟料中铝酸三钙(C3A)的含量,利用C3A水化速度快、早期强度高的特性,以及保水性强、粘性大的特点。复配保水增稠型水泥掺合材料,其中石灰石粉为粉煤灰水化提供成核基底,二者反应生成水化碳铝酸钙,提高胶凝材料早期强度与流动度,而超细海泡石粉凭借其巨大的比表面积和纤维状结构,显著提高水泥浆体粘度,通过内部养护作用蓄存水分、防止干缩开裂。助磨剂中多元醇胺可提高水泥早期强度,纤维素醚优异的保水作用,多功能助磨剂优化了水泥的粉磨效率及颗粒级配。结合以优化水泥矿物组成为基础、以精选多元掺合材料为支撑、以复配保水型助磨剂为保障,三条技术路线协同调控,赋予水泥兼具早强、低收缩、高保水、强粘性的综合性能优势。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to a plain masonry plastering mortar for home decoration and its preparation method. Background Technology
[0002] Masonry mortar and plastering mortar are the two most widely used cement-based building materials in home decoration projects. Masonry mortar is used for bonding and laying bricks, blocks, and other materials in walls, forming the framework of the building's enclosure structure; plastering mortar is used to coat the surface of masonry or concrete base layers, serving to level, protect, and decorate the base layer. In home decoration projects, due to cost and ease of operation considerations, a large amount of on-site manually mixed plain mortar (i.e., ordinary mortar without polymer admixtures) is used.
[0003] However, on-site mixing methods have many inherent drawbacks. On the one hand, the sources of raw materials such as cement and sand are complex and their quality fluctuates greatly. In particular, the mud content and particle size distribution of sand often fail to meet standard requirements, resulting in unstable key properties of the mixed mortar, such as strength, water retention, and adhesion, which directly affects construction quality and efficiency. On the other hand, hollow areas and cracking are the most common quality problems in masonry and plastering projects. The main reason is that traditional plain mortar has insufficient water retention, leading to incomplete cement hydration, low interfacial bond strength, and large mortar shrinkage, making it prone to cracking. Although existing technologies include solutions to improve mortar performance by adding polymer additives (such as redispersible latex powder, cellulose ether, starch ether, etc.), these organic additives contain a large number of surface-active components, which produce a significant air-entraining effect inside the mortar, leading to a sharp increase in the porosity of the hardened paste and a decrease in density, ultimately causing severe damage to the core mechanical properties of plain mortar, such as compressive strength and flexural strength. Secondly, the aforementioned organic additives generally have the negative effect of delaying cement hydration, which not only affects early strength development but also poses a quality hazard to the long-term durability and water resistance of mortar.
[0004] Therefore, considering the application scenarios of plain masonry plastering mortar for home decoration, developing a type of plain masonry plastering mortar that can simultaneously achieve high water retention, crack resistance, and bonding strength, while also being environmentally friendly and green, is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] The purpose of this invention is to overcome the aforementioned technical defects and deficiencies, and to provide a plain masonry plastering mortar for home decoration and its preparation method, achieving a unified design of masonry mortar and plastering mortar at the material level, thereby improving project quality and construction efficiency. Simultaneously, this invention uses high water retention, workability, early strength, and low shrinkage cement for home decoration, and introduces functional components into the formula, endowing the material with better workability and environmental characteristics while maintaining the basic properties of plain mortar.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A type of plain masonry plastering mortar for home decoration comprises the following raw materials by weight percentage: Cement content in home decoration: 10%~15%; Mineral admixtures 5%~8%; Manufactured sand 80%~85%; Home decoration cement is made by grinding the following materials in the following weight percentages: 56%~64% ordinary Portland cement clinker, 30%~40% admixtures, 2%~4% gypsum, and 0.05%~0.2% grinding aid; The mineral composition of ordinary silicate cement clinker includes: 40%~55% C3S, 20%~30% C2S, 8%~12% C3A, and 10%~15% C4AF; The admixture is composed of the following materials by mass percentage: 55%~65% fly ash, 31%~38% limestone, 3%~5% paper mill lime sludge, and 1%~2% ultrafine sepiolite powder; The grinding aid is composed of the following materials by weight percentage: 20%~25% diethanol monoisopropanolamine, 5%~10% triisopropanolamine, 1%~3% polyethylene glycol, 0.5%~1% hydroxyethyl methylcellulose, 3%~6% glycerol, 5%~10% anhydrous sodium sulfate, and 55%~60% water.
[0007] Furthermore, the mineral admixture is composed of the following materials by mass percentage: 35%~45% ultrafine attapulgite, 25%~55% activated lithium slag, and 10%~15% ultrafine metakaolin.
[0008] Furthermore, the ultrafine attapulgite, activated lithium slag, and metakaolin were each subjected to independent wet milling activation treatment.
[0009] Furthermore, the gradation of the manufactured sand is as follows: 17%~21% residue on a 3.35mm standard sieve, 23%~25% residue on a 2.36mm standard sieve, 10%~13% residue on a 1.18mm standard sieve, 9%~13% residue on a 0.63mm standard sieve, 13%~15% residue on a 0.315mm standard sieve, 17%~20% residue on a 0.16mm standard sieve, and 10%~13% residue on a 0.075mm standard sieve.
[0010] Furthermore, the fineness modulus of the manufactured sand is 2.5~3.2.
[0011] A method for preparing a plain masonry plastering mortar for home decoration includes the following steps: S1. Preparation of three independent wet-milled activated mineral powders: ultrafine attapulgite, activated lithium slag, and ultrafine metakaolin. S2. Mix the three mineral powders obtained in S1 evenly according to the ratio to obtain a mineral admixture; S3. Weigh the cement, manufactured sand and mineral admixtures according to the proportion, put them into the double spiral dry mixer and mix for 5 min to 10 min, seal and package to obtain the plain masonry plastering mortar for home decoration.
[0012] Further, in S1, the preparation method of ultrafine attapulgite is as follows: the purified attapulgite ore is dried to a moisture content of <2%, and water is added at a liquid-to-solid mass ratio of 3:1 to form a slurry with a solid content of 20%~28%; the horizontal ball mill is operated at a speed of 250r / min~400r / min for a wet milling time of 90min~180min, and the slurry temperature is controlled to be ≤55℃; after wet milling, the solid phase D50 of the slurry is ≤0.8μm, and it is spray-dried at 105℃ to obtain ultrafine attapulgite.
[0013] Further, in S1, the method for preparing activated lithium slag is as follows: the sulfuric acid process lithium slag is coarsely crushed to a particle size ≤1mm and dried to a moisture content <10%; water is added at a liquid-to-solid mass ratio of 2:1 to form a slurry with a solid content of 28%~40%; the slurry is wet-milled at a speed of 200r / min~350r / min for 60min~150min, and the slurry temperature is controlled to be ≤60℃; the output solid phase D50 is ≤3.0μm, and the activated lithium slag is obtained by spray drying.
[0014] Furthermore, in S1, the preparation method of ultrafine metakaolin is as follows: the metakaolin raw powder obtained by calcination at 700℃~850℃ is mixed into a slurry with a liquid-solid mass ratio of 2.5:1 and a ball-material mass ratio of 5:1~10:1, wet-milled for 30min~60min, and dried to obtain ultrafine metakaolin with D50≤1.2μm.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention improves the water retention performance of cement from multiple dimensions. By appropriately increasing the content of tricalcium aluminate (C3A) in the clinker of cement for home decoration, it utilizes the characteristics of C3A, such as rapid hydration, high early strength, strong water retention, and high viscosity. A compound water-retaining and thickening cement admixture is added. Limestone powder provides a nucleation substrate for fly ash hydration, and the two react to form hydrated calcium carboaluminate, improving the early strength and fluidity of the cementitious material. Ultrafine sepiolite powder, with its huge specific surface area and fibrous structure, significantly increases the viscosity of the cement paste, retaining moisture and preventing drying shrinkage and cracking through internal curing. Polyol amines in the grinding aid can improve the early strength of cement, and cellulose ethers have excellent water retention properties. This multifunctional grinding aid optimizes the grinding efficiency and particle size distribution of cement. Combining the optimization of cement mineral composition, the selection of multi-component admixtures, and the compound water-retaining grinding aid, these three technical routes work synergistically to endow cement with comprehensive performance advantages including early strength, low shrinkage, high water retention, and strong viscosity.
[0016] 2. Optimized composite multi-mineral admixtures are used to improve various performance indicators of mortar while reducing cement usage. The three minerals are activated by independent and differentiated mechanical wet grinding with exclusive grinding parameters, ensuring the integrity of attapulgite rod crystals, activation of lithium slag glass, and integrity of metakaolinite flaky crystals. After wet grinding, spray drying is performed to retain the active sites on the mineral surface. When dry-mixed into the mortar, it quickly forms a composite inorganic colloid-hydration gel dual network upon contact with water, simultaneously improving early strength, water retention, and hardened bond strength.
[0017] Specifically, under certain wet grinding parameters, attapulgite can be dispersed into single or a few rod-shaped crystal bundles with high aspect ratios. Lithium slag can refine the particles, increase the specific surface area, and also induce lattice distortion and bond breakage on the particle surface, stimulating activity. Metakaolin can be further exfoliated and refined, thereby exposing more reactive surfaces and edge broken bonds. Due to their huge specific surface area and surface charge, attapulgite rod crystals can disperse rapidly upon contact with water and interlock through hydrogen bonds between hydroxyl groups (-OH) to form a three-dimensional inorganic colloidal network structure. Lithium slag and metakaolin provide highly active silica-alumina components, which react in the alkaline environment and Ca2+ produced by cement hydration. 2+ Under stimulation, a rapid volcanic ash reaction occurs, reacting with Ca(OH)₂ to generate additional cementing products such as hydrated calcium silicate (CSH) gel and hydrated calcium aluminate. The inorganic colloidal network of attapulgite provides nucleation sites and growth space for the hydration reactions of lithium slag and metakaolinite; while the newly generated hydration products such as CSH gel can firmly bind these dispersed rod-shaped crystals together, forming an interpenetrating and synergistically reinforcing organic whole.
[0018] 3. This invention further incorporates the continuous gradation design of manufactured sand, effectively reducing mortar segregation and bleeding, significantly improving water retention capacity, and lowering the risk of cracking in the plaster layer due to drying shrinkage. It is particularly suitable for thin-layer masonry and plastering construction in home decoration, possessing the comprehensive advantages of high strength, high water retention, strong adhesion, and low shrinkage.
[0019] Specifically, the continuous gradation of manufactured sand, based on the close packing of coarse, micro, and nano-sized particles, can significantly reduce the porosity of the system and substantially improve compressive strength. The rough texture of the manufactured sand particles and the synergistic effect of the pozzolanic activity of the admixtures optimize the interfacial transition zone, enhancing the aggregate-paste interface bond strength and preventing strength reduction. Simultaneously, the continuous gradation design reduces the enrichment channels for free water in the paste. Combined with the physical water storage of sepiolite and the chemical water retention of hydroxyethyl methyl cellulose, this allows plain mortar prepared solely with cement and graded sand to possess excellent water retention properties without any traditional admixtures. This effectively inhibits segregation and bleeding, significantly reducing the risk of drying shrinkage and cracking in the plaster layer. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0021] Example 1, as a preferred embodiment of the present invention, provides a plain masonry plastering mortar for home decoration, the components and contents of which are as follows: Cement for home decoration: 15%; Mineral admixtures: 5%; Manufactured sand: 80%.
[0022] The cement for home decoration is made by grinding the following materials in the following weight percentages: 62% ordinary Portland cement clinker, 35% admixtures, 2.9% gypsum and 0.1% grinding aid.
[0023] The admixture consists of the following materials by mass percentage: 58% fly ash, 35% limestone, 5% paper mill lime sludge, and 2% ultrafine sepiolite powder.
[0024] The grinding aid is composed of the following materials by weight percentage: 22% diethanol monoisopropanolamine, 7% triisopropanolamine, 2% polyethylene glycol, 0.7% hydroxyethyl methylcellulose, 4% glycerol, 8% anhydrous sodium sulfate and 56.3% water.
[0025] The mineral admixture is composed of the following materials by mass percentage: 40% ultrafine attapulgite, 48% activated lithium slag and 12% ultrafine metakaolin.
[0026] The gradation of manufactured sand is as follows: 19% residue on a 3.35mm standard sieve, 24% residue on a 2.36mm standard sieve, 12% residue on a 1.18mm standard sieve, 11% residue on a 0.63mm standard sieve, 14% residue on a 0.315mm standard sieve, 18% residue on a 0.16mm standard sieve, and 12% residue on a 0.075mm standard sieve.
[0027] The fineness modulus of manufactured sand is 2.8.
[0028] The plain masonry plastering mortar for home decoration in this embodiment is prepared according to the following steps: S1. Prepare three independent wet-milled activated mineral powders respectively: S1-1 Preparation of ultrafine attapulgite: The purified attapulgite ore was dried to a moisture content of <2%, and water was added at a liquid-to-solid mass ratio of 3:1 to prepare a slurry with a solid content of 25%. The slurry was wet-milled at a speed of 300 r / min for 120 min, and the slurry temperature was controlled to be ≤55℃. After wet milling, the solid phase D50 of the slurry was ≤0.8μm. The slurry was then spray-dried at 105℃ to obtain ultrafine attapulgite.
[0029] Preparation of S1-2 activated lithium slag: The sulfuric acid process lithium slag is coarsely crushed to a particle size ≤1mm and dried to a moisture content <10%; water is added at a liquid-to-solid mass ratio of 2:1 to make a slurry with a solid content of 35%; the rotation speed is 280r / min, the wet grinding time is 100min, and the slurry temperature is controlled to ≤60℃; the output solid phase D50 is ≤3.0μm, and the slurry is spray-dried to obtain activated lithium slag.
[0030] S1-3 Preparation of ultrafine metakaolin dispersion: The metakaolin raw powder obtained by calcination at 750℃ was mixed into a slurry with a liquid-to-solid mass ratio of 2.5:1 and a ball-to-material mass ratio of 8:1. The mixture was wet-milled for 45 minutes and dried to obtain ultrafine metakaolin with D50≤1.2μm.
[0031] S2. Compound activated mineral admixture: The three powders obtained in steps S1-1, S1-2 and S1-3 are uniformly mixed at a ratio of 40%:48%:12% to obtain the mineral admixture.
[0032] S3. Dry-mixed masonry plastering mortar: Weigh the cement, manufactured sand and mineral admixtures according to the proportion, put them into a double-screw dry mixer and mix for 8 minutes, then seal and package to obtain the plain masonry plastering mortar for home decoration.
[0033] Example 2, as a preferred embodiment of the present invention, provides a plain masonry plastering mortar for home decoration, the components and contents of which are as follows: Cement for home decoration: 12%; Mineral admixtures: 8%; Manufactured sand: 80%.
[0034] The cement for home decoration is made by grinding the following materials in the following weight percentages: 60% ordinary Portland cement clinker, 36% admixtures, 3.9% gypsum and 0.1% grinding aid.
[0035] The admixture consists of the following materials by mass percentage: 55% fly ash, 38% limestone, 5% paper mill lime sludge, and 2% ultrafine sepiolite powder.
[0036] The grinding aid is composed of the following materials by weight percentage: 20% diethanol monoisopropanolamine, 10% triisopropanolamine, 3% polyethylene glycol, 1% hydroxyethyl methylcellulose, 3% glycerol, 5% anhydrous sodium sulfate and 58% water.
[0037] The mineral admixture is composed of the following materials by mass percentage: 35% ultrafine attapulgite, 55% activated lithium slag and 10% ultrafine metakaolin.
[0038] The gradation of manufactured sand is as follows: 17% residue on a 3.35mm standard sieve, 23% residue on a 2.36mm standard sieve, 10% residue on a 1.18mm standard sieve, 9% residue on a 0.63mm standard sieve, 13% residue on a 0.315mm standard sieve, 17% residue on a 0.16mm standard sieve, and 10% residue on a 0.075mm standard sieve.
[0039] The fineness modulus of manufactured sand is 2.5.
[0040] The preparation method of this embodiment is the same as that of Example 1, except that each component is weighed according to the above proportions, and the horizontal ball mill speed is 250 r / min and the wet milling time is 180 min in S1-1, the speed is 200 r / min and the wet milling time is 150 min in S1-2, the ball-to-material mass ratio is 10:1 and the wet milling time is 60 min in S1-3, and the mixing time is 10 min in S3.
[0041] Example 3, as a preferred embodiment of the present invention, provides a plain masonry plastering mortar for home decoration, the components and contents of which are as follows: Cement for home decoration: 13%; Mineral admixtures: 5%; Manufactured sand: 82%.
[0042] The cement for home decoration is made by grinding the following materials in the following weight percentages: 62% ordinary Portland cement clinker, 35% admixtures, 2.95% gypsum and 0.05% grinding aid.
[0043] The admixture consists of the following materials by mass percentage: 60% fly ash, 35% limestone, 3% paper mill lime sludge, and 2% ultrafine sepiolite powder.
[0044] The grinding aid is composed of the following materials by weight percentage: 25% diethanol monoisopropanolamine, 5% triisopropanolamine, 1% polyethylene glycol, 0.5% hydroxyethyl methylcellulose, 6% glycerol, 7% anhydrous sodium sulfate and 55.5% water.
[0045] The mineral admixture is composed of the following materials by mass percentage: 45% ultrafine attapulgite, 40% activated lithium slag and 15% ultrafine metakaolin.
[0046] The gradation of manufactured sand is as follows: 21% residue on a 3.35mm standard sieve, 25% residue on a 2.36mm standard sieve, 13% residue on a 1.18mm standard sieve, 13% residue on a 0.63mm standard sieve, 15% residue on a 0.315mm standard sieve, 20% residue on a 0.16mm standard sieve, and 13% residue on a 0.075mm standard sieve.
[0047] The fineness modulus of the manufactured sand is 3.2.
[0048] The preparation method of this embodiment is the same as that of Example 1, except that each component is weighed according to the above proportions, and the horizontal ball mill speed is 400 r / min and the wet milling time is 90 min in S1-1, the speed is 350 r / min and the wet milling time is 60 min in S1-2, the ball-to-material mass ratio is 5:1 and the wet milling time is 30 min in S1-3, and the mixing time is 5 min in S3.
[0049] Example 4, as a preferred embodiment of the present invention, provides a plain masonry plastering mortar for home decoration, the components and contents of which are as follows: Cement for home decoration: 10%; Mineral admixtures: 5%; Manufactured sand: 85%.
[0050] The cement for home decoration is made by grinding the following materials in the following weight percentages: 62% ordinary Portland cement clinker, 34% admixtures, 3.8% gypsum and 0.2% grinding aid.
[0051] The admixture consists of the following materials by mass percentage: 60% fly ash, 33% limestone, 5% paper mill lime sludge, and 2% ultrafine sepiolite powder.
[0052] The grinding aid is composed of the following materials by weight percentage: 23% diethanol monoisopropanolamine, 6% triisopropanolamine, 2.5% polyethylene glycol, 0.8% hydroxyethyl methylcellulose, 5% glycerol, 7% anhydrous sodium sulfate and 55.7% water.
[0053] The mineral admixture is composed of the following materials by mass percentage: 38% ultrafine attapulgite, 50% activated lithium slag and 12% ultrafine metakaolin.
[0054] The gradation of manufactured sand is as follows: 20% residue on a 3.35mm standard sieve, 24% residue on a 2.36mm standard sieve, 12% residue on a 1.18mm standard sieve, 11% residue on a 0.63mm standard sieve, 14% residue on a 0.315mm standard sieve, 19% residue on a 0.16mm standard sieve, and 12% residue on a 0.075mm standard sieve.
[0055] The fineness modulus of manufactured sand is 2.9.
[0056] The preparation method of this embodiment is the same as that of embodiment 1, except that each component is weighed according to the above ratio, and the mixing time in S3 is 7 min.
[0057] Example 5, as a preferred embodiment of the present invention, provides a plain masonry plastering mortar for home decoration, the components and contents of which are as follows: Cement for home decoration: 12%; Mineral admixtures: 6%; Manufactured sand: 82%.
[0058] The cement for home decoration is made by grinding the following materials in the following weight percentages: 56% ordinary Portland cement clinker, 40% admixtures, 3.8% gypsum and 0.2% grinding aid.
[0059] The admixture consists of the following materials by mass percentage: 65% fly ash, 31% limestone, 3% paper mill lime sludge, and 1% ultrafine sepiolite powder.
[0060] The grinding aid is composed of the following materials by weight percentage: 21% diethanol monoisopropanolamine, 8% triisopropanolamine, 1.5% polyethylene glycol, 0.6% hydroxyethyl methylcellulose, 4.5% glycerol, 9% anhydrous sodium sulfate and 55.4% water.
[0061] The mineral admixture is composed of the following materials by mass percentage: 42% ultrafine attapulgite, 45% activated lithium slag and 13% ultrafine metakaolin.
[0062] The gradation of manufactured sand is as follows: 18% residue on a 3.35mm standard sieve, 24% residue on a 2.36mm standard sieve, 11% residue on a 1.18mm standard sieve, 10% residue on a 0.63mm standard sieve, 14% residue on a 0.315mm standard sieve, 18% residue on a 0.16mm standard sieve, and 11% residue on a 0.075mm standard sieve.
[0063] The fineness modulus of manufactured sand is 2.7.
[0064] The preparation method of this embodiment is the same as that of Example 1, except that each component is weighed according to the above ratio, and the mixing time in S3 is 6 min.
[0065] Comparative Example 1 provides a plain masonry plastering mortar for home decoration. The difference between this mortar and Example 1 is that ordinary 42.5 grade silicate cement is used to replace an equal amount of home decoration cement and mineral admixtures. The remaining components and preparation methods are the same as in Example 1.
[0066] Comparative Example 2 provides a plain masonry plastering mortar for home decoration. The difference between it and Example 1 is that the ultrafine attapulgite, activated lithium slag and ultrafine metakaolin in the mineral admixtures are not independently wet-milled and activated, but are directly mixed in the same proportion as unactivated raw powder. The other components and preparation methods are the same as in Example 1.
[0067] Specifically, the attapulgite ore was only dried and crushed, without wet milling activation; the lithium slag was only coarsely crushed and dried, without wet milling activation; and the metakaolin was only calcined, without wet milling dispersion. The three powders were directly mixed according to the proportions in Example 1 and used as a composite mineral admixture. The remaining components and preparation methods were the same as in Example 1.
[0068] Comparative Example 3 provides a plain masonry plastering mortar for home decoration. The difference between this mortar and Example 1 is that the admixtures in the cement for home decoration do not contain paper mill lime sludge and ultrafine sepiolite powder. The remaining components and preparation methods are the same as in Example 1.
[0069] Comparative Example 4 provides a plain masonry plastering mortar for home decoration. The difference between it and Example 1 is that the gradation of the manufactured sand exceeds the range defined by this invention, and the fineness modulus is 1.8. The other components and preparation methods are the same as in Example 1.
[0070] Specifically, the gradation of the manufactured sand in this comparative example is as follows: 5% residue on a 3.35mm standard sieve, 12% residue on a 2.36mm standard sieve, 18% residue on a 1.18mm standard sieve, 22% residue on a 0.63mm standard sieve, 20% residue on a 0.315mm standard sieve, 13% residue on a 0.16mm standard sieve, and 10% residue on a 0.075mm standard sieve, with a fineness modulus of 1.8. The remaining components and preparation methods are the same as in Example 1.
[0071] Comparative Example 5 provides a plain masonry plastering mortar for home decoration. The difference between it and Example 1 is that the proportion of mineral admixtures exceeds the range defined by this invention. Specifically, it consists of 60% ultrafine attapulgite, 20% activated lithium slag, and 20% ultrafine metakaolin. The remaining components and preparation methods are the same as in Example 1.
[0072] Performance testing was conducted on the plain masonry plastering mortars prepared in Examples 1-5 and Comparative Examples 1-5. The testing methods followed JGJ 70-2009 "Test Methods for Basic Properties of Building Mortar". The test items included: compressive strength, consistency, setting time, water retention rate, shrinkage rate, and tensile bond strength. The test results for each example and comparative example are shown in Table 1.
[0073] Table 1 Test Results
[0074] As shown in Table 1, Example 1 exhibits the best overall performance, with a shrinkage rate of only 0.0738%, a tensile bond strength of 0.355 MPa, and a water retention rate as high as 94.3%. All indicators are significantly better than the national standard requirements (shrinkage rate ≤ 0.2%, bond strength ≥ 0.20 MPa, water retention rate ≥ 88%). In contrast, Comparative Example 1 performs the worst, with a shrinkage rate as high as 0.1706%, a bond strength of only 0.187 MPa, and a water retention rate of only 86.1%, failing to meet the national standard requirements for both bond strength and water retention rate. Overall, the shrinkage rate and bond strength of all examples are significantly better than those of the comparative example, indicating that the patented formula has significant advantages in controlling volume stability and enhancing interfacial adhesion.
[0075] Finally, it should be noted that the above embodiments are merely preferred embodiments of the present invention used to illustrate the technical solutions of the present invention, and are not intended to limit the invention, nor are they intended to limit the patent scope of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. That is to say, any changes or refinements made to the main design concept and spirit of the present invention that are not of substantial significance, but whose technical problems are still consistent with the present invention, should be included within the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention to other related technical fields are similarly included within the patent protection scope of the present invention.
Claims
1. A type of plain masonry plastering mortar for home decoration, characterized in that, Raw materials include the following percentage by weight: Cement content in home decoration: 10%~15%; Mineral admixtures 5%~8%; Manufactured sand 80%~85%; Home decoration cement is made by grinding the following materials in the following weight percentages: 56%~64% ordinary Portland cement clinker, 30%~40% admixtures, 2%~4% gypsum, and 0.05%~0.2% grinding aid; The mineral composition of ordinary silicate cement clinker includes: 40%~55% C3S, 20%~30% C2S, 8%~12% C3A, and 10%~15% C4AF; The admixture is composed of the following materials by mass percentage: 55%~65% fly ash, 31%~38% limestone, 3%~5% paper mill lime sludge, and 1%~2% ultrafine sepiolite powder; The grinding aid is composed of the following materials by weight percentage: 20%~25% diethanol monoisopropanolamine, 5%~10% triisopropanolamine, 1%~3% polyethylene glycol, 0.5%~1% hydroxyethyl methylcellulose, 3%~6% glycerol, 5%~10% anhydrous sodium sulfate, and 55%~60% water.
2. The plain masonry plastering mortar for home decoration according to claim 1, characterized in that, The mineral admixture is composed of the following materials by mass percentage: 35%~45% ultrafine attapulgite, 25%~55% activated lithium slag, and 10%~15% ultrafine metakaolin.
3. The plain masonry plastering mortar for home decoration according to claim 2, characterized in that, Ultrafine attapulgite, activated lithium slag, and metakaolin were each subjected to independent wet milling and activation treatment.
4. The plain masonry plastering mortar for home decoration according to claim 1, characterized in that, The gradation of manufactured sand is as follows: 17%~21% residue on a 3.35mm standard sieve, 23%~25% residue on a 2.36mm standard sieve, 10%~13% residue on a 1.18mm standard sieve, 9%~13% residue on a 0.63mm standard sieve, 13%~15% residue on a 0.315mm standard sieve, 17%~20% residue on a 0.16mm standard sieve, and 10%~13% residue on a 0.075mm standard sieve.
5. The plain masonry plastering mortar for home decoration according to claim 1, characterized in that, The fineness modulus of manufactured sand is 2.5~3.
2.
6. A method for preparing a plain masonry plastering mortar for home decoration according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Preparation of three independent wet-milled activated mineral powders: ultrafine attapulgite, activated lithium slag, and ultrafine metakaolin. S2. Mix the three mineral powders obtained in S1 evenly according to the ratio to obtain a mineral admixture; S3. Weigh the cement, manufactured sand and mineral admixtures according to the proportion, put them into the double spiral dry mixer and mix for 5 min to 10 min, seal and package to obtain the plain masonry plastering mortar for home decoration.
7. The preparation method according to claim 6, characterized in that, In S1, the preparation method of ultrafine attapulgite is as follows: the purified attapulgite ore is dried to a moisture content of <2%, and water is added at a liquid-to-solid mass ratio of 3:1 to make a slurry with a solid content of 20%~28%; the horizontal ball mill is operated at a speed of 250r / min~400r / min for a wet milling time of 90min~180min, and the slurry temperature is controlled to be ≤55℃; after wet milling, the solid phase D50 of the slurry is ≤0.8μm, and it is spray-dried at 105℃ to obtain ultrafine attapulgite.
8. The preparation method according to claim 6, characterized in that, In S1, the preparation method of activated lithium slag is as follows: the sulfuric acid process lithium slag is coarsely crushed to a particle size ≤1mm and dried to a moisture content <10%; water is added at a liquid-to-solid mass ratio of 2:1 to form a slurry with a solid content of 28%~40%; the rotation speed is 200r / min~350r / min, wet milling is performed for 60min~150min, and the slurry temperature is controlled to ≤60℃; the output solid phase D50 is ≤3.0μm, and the activated lithium slag is obtained by spray drying.
9. The preparation method according to claim 6, characterized in that, In S1, the preparation method of ultrafine metakaolin is as follows: the metakaolin raw powder obtained by calcination at 700℃~850℃ is mixed into a slurry with a liquid-solid mass ratio of 2.5:1 and a ball-material mass ratio of 5:1~10:1, wet-milled for 30min~60min, and dried to obtain ultrafine metakaolin with D50≤1.2μm.